Les emplois corrélatifs de parfois, quelquefois et des fois - Anne-Marie Guiraud (Discours)
We will study the correlative uses of the forms parfois (sometimes), quelquefois (now and then), des fois (several times) and how they mark the boundaries of a segment of discourse. After having identified the semantic and syntactical properties of these forms when used on their own, we will then define the characteristics of the correlations established with parfois, quelquefois and des fois. We will draw on a corpus from the 16th through the 20th century from the FRANTEXT online library, including utterances which we expect will meet our criteria and we will discuss the semantic and syntactical characteristics of these forms in correlative uses. We will finally compare the properties of parfois, quelquefois, des fois used on their own and in their correlative uses in order to highlight their differences.